Evaluation of Faculty-School Partnership Model: Pre-service Science Teachers’ Views - (:unkn) unknown (My University, 2010)
0

Field experience has been regarded as the most favorably viewed component of initial teacher education in contributing to pre-service teachers’ professional learning. The concept of university–school partnerships is promoted as a holistic approach where mutual professional learning benefits are anticipated and realized—where the knowledge and expertise of educators in schools and universities are valued, respected and utilized. While the partnerships may serve many aims, the underlying belief in their value often stems from the generally held assumption that such partnerships provide opportunities for the relationships between theory and practice to be more effectively enhanced. Varying periods of placement in school and classroom settings encourage pre-service teachers to engage in a developmental process of observing and experimenting with teaching practice, and learning about the skills, knowledge, philosophies and attitudes of the professional teacher. Therefore, the quality of pre-service teachers’ learning experiences in the field is a major concern in initial teacher education. Improving science teacher education has been an integral part of reform movements in the National Education in Turkey during the last decade. As a result of these efforts, Higher Education Council and Ministry of National Education restructured science education
Keywords: Eğitim, Eğitim Araştırmaları